2012
DOI: 10.1051/0004-6361/201219374
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of very low-mass stars and brown dwarfs in the Lambda Orionis star-forming region

Abstract: Context. Most observational studies conducted so far point toward brown dwarfs sharing a similar formation mechanism as the one that is accepted for low-mass stars. However, larger databases and more systematic studies are needed before strong conclusions can be reached. Aims. In this second paper of a series devoted to studying the spectroscopic properties of the Lambda Orionis star-forming region members, we study accretion, activity and rotation for a wide set of spectroscopically confirmed members of the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 54 publications
1
67
3
Order By: Relevance
“…Collinder 69 presents several advantages for the purpose of our study. It is well studied and an extensive list of more than 200 spectroscopically confirmed members is available (Bayo et al 2012). Photometry in almost all the bands presented in the current study has been obtained for its members, making the comparison possible over a broad domain of colors and luminosities.…”
Section: Comparison With Collinder 69mentioning
confidence: 99%
“…Collinder 69 presents several advantages for the purpose of our study. It is well studied and an extensive list of more than 200 spectroscopically confirmed members is available (Bayo et al 2012). Photometry in almost all the bands presented in the current study has been obtained for its members, making the comparison possible over a broad domain of colors and luminosities.…”
Section: Comparison With Collinder 69mentioning
confidence: 99%
“…Numerical simulations of planetary population synthesis, such as the ones led by Alibert et al (2011) and Mordasini et al (2012) have shown that the expected planet population should depend on the stellar masses and disk properties. There has been a general effort to better characterize the relationship between the stellar masses and disk properties, which can additionally be related to the formation mechanism of very low-mass stars (Padoan & Nordlund 2002;Reipurth & Clarke 2001;Bayo et al 2011Bayo et al , 2012. It is therefore of prime importance for better constraining the disk characteristics, as well as dust and gas properties, around stars over a wide range of masses (e.g., Pascucci et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Duerr et al (1982) identified three associations within a very large bubble seen in Hα, later on photometric and spectroscopically characterized by Dolan & Mathieu (1999. Deeper photometry and spectroscopy well inside the substellar domain have been published by Barrado y Navascués et al (2004a, 2007a and Bayo et al (2011Bayo et al ( , 2012.…”
Section: A Rising "Star": Lambda Orionis Star Forming Regionmentioning
confidence: 85%
“…Again, just to provide some references: NGC2516 and M35, almost Pleiades twins (Jeffries et al 1998;Barrado y Navascués et al 2001a), IC2602 and IC2391 (Barrado y Navascués et al 1999aRandich 2001;Randich et al 2001;Barrado y Navascués et al 2004b), NGC2547 , IC4665 ), and Collinder 69 (Dolan & Mathieu 1999, Bayo et al 2012). In the very near future, the large scale spectroscopic survey Gaia-ESO (Gilmore et al 2012;Randich et al 2013) will provide an extended database.…”
Section: Sizes: Eclipsing Binariesmentioning
confidence: 99%